Fostering a Collegial Department: Strategies for Success - Robert E. Cipriano Dr. (Academic Chairpersons Conference Proceedings, 2018)
This interactive workshop will operationally define collegiality, and through case studies will provide strategies to be used to foster a collegial department. Attendees will actively participate in problem solving activities designed to provide attendees with proven methods of facilitating a collegial department. Presentation will share data regarding collegiality from an 11-year study of department chairs.
Keywords: Foster Collegial Department Strategies Success